Structural and microstructural features of lead‐free BNT–BT thin films: Nanoscale electromechanical response analysis. Issue 7 (24th February 2021) - Mendez‐González, Yanela; Ferri, Anthony; Lima, Elton C.; Hamieh, Ahmad; Remiens, Denis; Peláiz‐Barranco, Aimé; Silva, Atair C.; de los Santos Guerra, José
Abstract: The structural, microstructural, and electromechanical properties have been investigated at the nanoscale, as a function of the lanthanum concentration, in Bi0.506 Na0 .46 Ba0.08–3 x /2 La x TiO3 ( x  = 0, 2 and 3 at %) (BNLBT– x ) lead‐free thin films. The structural characterization, investigated from X‐ray diffraction and Raman spectroscopy, confirmed the formation of the perovskite structure and suggests the coexistence of both antiferroelectric (tetragonal) and ferroelectric (rhombohedral) phases. The surface morphology, characterized by atomic force microscopy, has shown a dense and crack‐free nanostructured surface for all the studied compositions, noting that the increase in the lanthanum content promoted a decrease in both the grain size and surface roughness. PFM imaging analyses have evidenced the ferroelectric domain structure over the surface, as well as the presence of non–piezoelectric regions attributed to the antiferroelectric phase. PFM spectroscopy measurements revealed a reliable switching behavior for locally probed ferroelectric domains, yielding a noticeable local piezoactivity, which indeed shows to increase with the increase in the doping content. The static domain wall was also analyzed in terms of the nanoscale domain structure, and the obtained dimensionality indicated a local electric field‐induced structural disorder. The clear local piezo/ferroelectric nature highlighted on the studied materials underlines the potential for applications of the BNLBT– x films for their integration into advanced electronic nanodevices.